2021
DOI: 10.1007/s10646-021-02458-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of the insecticide abamectin and the fungicide difenoconazole (individually and in mixture) to the tropical stingless bee Melipona scutellaris

Abstract: Stingless bees have been recognized as essential plant pollinators and producers of various natural products in neotropical areas. Research into the potential risks of pesticides they may be exposed to in agricultural fields, however, remains meagre. Especially the toxicity of pesticide mixtures likely to occur under real-world conditions and that are likely to exert synergetic effects has been poorly studied. The aim of the present study was therefore to evaluate the single and mixture acute contact and oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The data from this study were validated by the results of tests with the positive control Dimethoate AS, which is a reference for toxicity standards and indicated the sensitivity of M. interrupta bees to its active ingredient. The CL50 for Dimethoate recorded here was the lowest among Melipona bees compared to available data in the literature for Melipona quadrifasciata Lepeletier, 1836 (Hymenoptera: Apidae) (Piovesan et al 2020) and Melipona scutellaris Latreille, 1811 (Hymenoptera: Apidae) (Brigante et al 2021) (Table 1). It was also lower than for non-Melipona bees, such as Scaptotrigona postica (Latreille, 1807) (Hymenoptera: Apidae) (Jacob et al 2019b).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The data from this study were validated by the results of tests with the positive control Dimethoate AS, which is a reference for toxicity standards and indicated the sensitivity of M. interrupta bees to its active ingredient. The CL50 for Dimethoate recorded here was the lowest among Melipona bees compared to available data in the literature for Melipona quadrifasciata Lepeletier, 1836 (Hymenoptera: Apidae) (Piovesan et al 2020) and Melipona scutellaris Latreille, 1811 (Hymenoptera: Apidae) (Brigante et al 2021) (Table 1). It was also lower than for non-Melipona bees, such as Scaptotrigona postica (Latreille, 1807) (Hymenoptera: Apidae) (Jacob et al 2019b).…”
Section: Discussionmentioning
confidence: 44%
“…Data related to toxicity tests using Thiamethoxam on stingless bees are still scarce. The information available for this group of bees is restricted to a few species such as M. scutellaris (Miotelo et al 2021;Brigante et al 2021), S. bipunctata (Moreira et al 2018), T. angustula (Jacob et al 2019a), M. quadrifasciata and Trigona fiebrigi (Schwarz, 1938) (Piovesan et al 2020. When it comes to Amazonian stingless bee species, the data from this study are unprecedented as there are no bibliographic records of research on the toxicity of chemical agents related to effects of insecticides with Amazonian meliponinios, most likely due to these species occurring in regions that are not extensively agricultural in tropical climate countries, and it is known that the main toxicity studies have been conducted in temperate climate countries (Moraes et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, application of Startect against fish-parasitizing acanthocephalans seems feasible. On the other hand, the second active ingredient of Startect, abamectin, has insecticide and acaricide activity [83,84]. Thus, dissipation of Startect into the environment might be problematic and the mere administration of derquantel might be the better choice in fish.…”
Section: Drugs Against Acanthocephalansmentioning
confidence: 99%
“…Due to the inhibition of mitochondrial respiration [ 33 ], the fungicide pyraclostrobin can affect essential functions of bee physiology. A few studies have shown the side effects of fungicides on non-target stingless bees [ 34 , 35 , 36 , 37 , 38 ], but there is still a considerable gap between insecticide and fungicide studies [ 25 ].…”
Section: Introductionmentioning
confidence: 99%